Experimental Study of Forced Convection Heat Transfer in a Tropical Greenhouse Using a Cooling Pad and Fan System - Deni Elham Prayoga; Abdul Gafur (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
A greenhouse is a cultivation technology designed to control environmental conditions to support optimal plant growth. However, in tropical regions such as Indonesia, the air temperature inside greenhouses tends to increase due to high solar radiation, making an effective cooling system essential. This study aims to evaluate the performance of a cooling pad and exhaust fan system in reducing air temperature, maintaining relative humidity, and achieving uniform temperature distribution through forced convection heat transfer inside a greenhouse. An experimental method was employed by measuring outdoor temperature, indoor temperature, relative humidity (RH), and air velocity at 12 sensor locations. Data were collected every 20 minutes from 08:00 to 16:00 for 28 consecutive days. The collected data were analyzed to determine the average temperature, temperature distribution, temperature reduction (ΔT), and cooling system effectiveness. The results indicate that the cooling pad and exhaust fan system reduced the indoor air temperature by an average of 4.25°C, maintained relative humidity within the range of 70–84%, and produced an air velocity between 0.90 and 1.12 m/s. The temperature distribution across the 12 sensor locations showed a maximum difference of only 0.3°C, indicating a uniform air distribution throughout the greenhouse. Therefore, the proposed cooling system is effective in controlling the greenhouse microclimate and has the potential to improve crop cultivation performance in tropical environments.